Panigarh cave stalagmite evidence of climate change in the Indian Central Himalaya since AD 1256: Monsoon breaks and winter southern jet depressions. (15th September 2015) - Liang, Fuyuan; Brook, George A.; Kotlia, Bahadur S.; Railsback, L. Bruce; Hardt, Benjamin; Cheng, Hai; Edwards, R. Lawrence; Kandasamy, Selvaraj
Abstract: Variations in petrography, stable isotopes, reflectance, and luminescence along the central growth axis of a 14.5 cm stalagmite from Panigarh cave indicate cooler and slightly wetter conditions in the Himalayan foothills of northern India during the Little Ice Age (LIA), which lasted from ∼AD 1489–1889 based on deposition of calcite, and AD 1450–1820 based on rapid changes in δ 18 O values. Conditions were warmer and drier during the preceding Medieval Climate Anomaly (MCA) and also in the post-LIA periods, as evidenced by deposition of aragonite. A review of currently existing stalagmite and other proxy data from south and east Asia reveals a broad spatial pattern in precipitation over south and east Asia during the LIA, with northern areas showing generally increased precipitation and southern areas reduced precipitation. During the MCA and after the LIA, the records suggest this pattern was reversed. Weaker ISM during the LIA brought drought conditions to the core ISM area but triggered more monsoon 'breaks' that brought higher precipitation to the Himalayas. At the same time, the weaker ISM may also have pushed more depressions along the path of the southern winter jet which brought more winter precipitation to the Himalayas and therefore a LIA wetter in our study area. Highlights: The Little Ice Age (LIA) was wetter in the Indian Central Himalaya but drier in the core Indian Summer Monsoon (ISM) area. The pattern was reversed during the Medieval Climate Anomaly (MCA) and the post-LIA periods. Weaker ISM during the LIA brought less precipitation thus drought conditions to the core ISM area. Weaker ISM during the LIA triggered more monsoon 'breaks' resulting in higher precipitation in Himalayas.